Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am following a quantum mechanics text book which uses a simple looking substitution in a derivative.

The substitution is $$\xi=\gamma x\tag1$$

It then says that $$\frac{d\psi}{dx}=\frac{d\psi}{d\xi}\frac{d\xi}{dx}=\gamma\frac{d\psi}{d\xi}\tag2$$

So far so good. Now comes the part I don't follow. It says: $$\frac{d^2\psi}{dx^2}=\gamma^2\frac{d^2\psi}{d\xi^2}\tag3$$

I don't know how they get this. I tried $$\frac{d^2\psi}{dx^2}=\frac{d^2\psi}{d\xi^2}\frac{d^2\xi}{dx^2}\tag4$$ but I get $$\frac{d^2\xi}{dx^2}=0$$ by using the substitution in equation (1). I'd appreciate it if someone could explain this to me.

Another thing I tried is (suggested by comment below): $$\frac{d}{dx}\left(\frac{d\psi}{dx}\right)=\frac{d}{dx}\left(\frac{d\psi}{d\xi}\frac{d\xi}{dx}\right)=\frac{d^2\psi}{dxd\xi}\frac{d\xi}{dx}+\frac{d\psi}{d\xi}\frac{d^2\xi}{dx^2}\tag5$$

Now since $$\frac{d^2\xi}{dx^2}=0$$ equation (5) reduces to:$$\frac{d}{dx}\left(\frac{d\psi}{dx}\right)=\frac{d}{dx}\left(\frac{d\psi}{d\xi}\frac{d\xi}{dx}\right)=\gamma\frac{d^2\psi}{dxd\xi}$$

Once again, I'm stuck..

share|cite|improve this question
(4) is wrong. You need to use (2) again, but with $d\psi/dx$ in $\psi$'s place. – Hans Lundmark Nov 28 '12 at 10:33

Ok, I got it.

$$\gamma\frac{d^2\psi}{dxd\xi}=\gamma\frac{d^2\psi}{d\xi dx}=\gamma \frac{d}{d\xi}\frac{d\psi}{dx}$$

$$\gamma \frac{d}{d\xi}\frac{d\psi}{dx}=\gamma \frac{d}{d\xi}\left(\gamma\frac{d\psi}{d\xi}\right)=\gamma^2\frac{d^2\psi}{d\xi^2}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.